Skin substitutes for extensive burn coverage in Togo: A retrospective study - Kouevi-Koko Têtê Edem; Amouzou Komla Séna; Bakriga Batarabadja; Amegble Koffi Jude Dzidzo; Dellanh Yaovi Yanick; Dosseh Ekoué David Joseph (Elsevier, 2021)
Four children, from 5 to 10 years aged, presented to the Sylvanus Olympio Hospital (SOTH) of Lomé (Togo) with severe (second- and third-degree) burns of 25-78% of total body surface area (TBSA) due to flame in domestic accidents and were treated using skin substitutes.We conducted skin substitution by dermal templates (Integra®) for two children and by skin allografts for the other two. In the two cases of dermal templates, we performed a wound excision on day 30 in one case, and on day 28 in the other. In one case, we associated the coverage with the dermal template to a negative pressure wound therapy; we applied skin graft on day 18 and day 21. In the follow-up, we observed no complication in both cases.In one of the two cases of skin allograft, we performed an eschar excision on day 8 and a donor skin allograft. we conducted another excision on day 15 while some parts were covered with skin autograft. The child died ten hours after the last procedure. The second patient had sequential excisions and coerage of some parts with skin allograft, and some others with skin autograft on day 42 In the fourth month, the child was discharged with a wound coverage of 74%, which was completed by another skin graft in the sixth month.The availability of dermal templates compelled the choice between the two skin substitutes. The access to other grafting options, such as a deceased skin bank, could allow the SOTH surgical team to step forward to the burn care.